2011
DOI: 10.1093/nar/gkr474
|View full text |Cite
|
Sign up to set email alerts
|

Diauxic shift-dependent relocalization of decapping activators Dhh1 and Pat1 to polysomal complexes

Abstract: Dhh1 and Pat1 in yeast are mRNA decapping activators/translational repressors thought to play key roles in the transition of mRNAs from translation to degradation. However, little is known about the physical and functional relationships between these proteins and the translation machinery. We describe a previously unknown type of diauxic shift-dependent modulation of the intracellular locations of Dhh1 and Pat1. Like the formation of P bodies, this phenomenon changes the spatial relationship between components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 43 publications
7
26
0
Order By: Relevance
“…Indeed, we and others have observed that Dhh1 binds ribosomes [38]. Moreover, Dhh1 represses translation in vitro of an mRNA harboring the Cricket Paralysis Virus IRES, which requires only 40S ribosomes to initiate translation [12].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Indeed, we and others have observed that Dhh1 binds ribosomes [38]. Moreover, Dhh1 represses translation in vitro of an mRNA harboring the Cricket Paralysis Virus IRES, which requires only 40S ribosomes to initiate translation [12].…”
Section: Discussionmentioning
confidence: 80%
“…We predicted that if endogenously expressed Dhh1 were performing the same function, Dhh1 should be found associated with polyribosomes. We and others have documented, however, that Dhh1 sediments with the soluble RNP in sucrose gradients [12],[38]. We reasoned that the association of Dhh1 with polyribosomes in cells with active decay machinery and minimal cues for translational repression (i.e.…”
Section: Resultsmentioning
confidence: 94%
“…An alternative source of altered mRNA stability can come from changes in the translation of mRNAs (Drummond et al, 2011; Huch and Nissan, 2014; Jacobson and Peltz, 1996). We therefore examined the polysome profiles of extracts from yeast exponentially growing in glucose to gain insight into their translation.…”
Section: Resultsmentioning
confidence: 99%
“…Yeast Dhh1 interacts physically with the Ccr4-Not complex (Hata et al, 1998;Coller et al, 2001;Maillet & Collart, 2002) and contributes to translational repression (Coller & Parker, 2005). Moreover, an interaction between Dhh1 and polysomes has been described (Drummond et al, 2011) and components of the Ccr4-Not complex including Not proteins and Dhh1 localize to cytoplasmic foci called P-bodies (Muhlrad & Parker, 2005;Parker & Sheth, 2007), where turnover of translationally repressed mRNA takes place. Indeed, we found that also Dhh1 contributes to the repression of K12 protein synthesis ( Fig 6B).…”
Section: Lysates Aggregatesmentioning
confidence: 99%